The Influence of Sustainable Tourists Destination Attractiveness and Tourism Marketing Strategy on Tourism Sustainability in South Sulawesi Indonesia - Adrianus S. Girikallo (Jurnal Riset Ekonomi dan Akuntansi, 2023)
The research aims to analyze the relationship between sustainable tourism destination attraction and sustainable tourism marketing strategy on tourism sustainability. The research was conducted in four districts/cities in South Sulawesi Province, namely Tana Toraja Regency, Parepare Municipality, Makassar Municipality and Toraja Utara Regency. This research uses a quantitative explanatory approach, applying a structural equation model with multiple regression analysis techniques. The data collection method was carried out by distributing online self-administered questionnaires using the Google form platform. In addition, structured interviews were carried out with visitors who were met at tourist attraction locations who were willing to be respondents. The amount of data collected was 350 domestic tourists consisting of 149 males and 201 females. The collected data was tested for validity and reliability using the SPSS-23 software. The test of CFA, measurement, structural, and goodness of fit model using the AMOS software version 23 with the maximum likelihood method. The results of hypothesis testing show that the relation of attractiveness sustainable tourism destinations and sustainable tourism marketing strategies on tourism sustainability has a significant effect on tourism sustainability. The contribution of this research is expected to provide an advantage to the government's policy related to sustainable tourism development strategies in South Sulawesi Indonesia.